KONTRIBUSI HUBUNGAN KERJA DAN KUALITAS DISIPLIN KERJA TERHADAP KEPUASAN PEGAWAI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SOLOK - Yeni, Afni; Sriyanti, Esi; Idris, Assabil (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to determine the Contribution of Work Discipline and Quality of Work Relations to Employee Satisfaction at the Solok City Population and Civil Registration Office with a sample of 32 respondents who were researched using a quantitative method. Based on the results of statistical analysis, it can be interpreted that Employment Relations partially have a significant effect on Job Satisfaction, this is evidenced by the t-test with a significant value of 3.657 > 2.045 in the value of the significance level, 0.001 < 0.05. So it can be interpreted that Employment Relations have a significant effect on Job Satisfaction. Based on the results of statistical analysis, it can be concluded that Work Discipline partially has a significant effect on Job Satisfaction at the Solok City Population and Civil Registration Office. This is evidenced by the T test with a significant value of 4.716 > t table 2.045 and a significance value of 0.000 < 0.05. So it can be concluded that Work Discipline has a significant effect on Job Satisfaction. Simultaneously, Labor Relations and Work Discipline have a significant effect on Job Satisfaction at the Solok City Population and Civil Registration Office. This is evidenced by using the F test with a significant value  of 41.337 > 3.33 and a significant value of 0.000 and this value is much smaller than a (0.05). This can also be seen from the R Square value obtained at 0.740 or 74% and the remaining 26% is influenced by other variables that are not included in this study